Ultrafast measurements of the dynamics of single nanostructures: a review. (28th November 2018) - Beane, Gary; Devkota, Tuphan; Brown, Brendan S; Hartland, Gregory V
Abstract: The ability to study single particles has revolutionized nanoscience. The advantage of single particle spectroscopy measurements compared to conventional ensemble studies is that they remove averaging effects from the different sizes and shapes that are present in the samples. In time-resolved experiments this is important for unraveling homogeneous and inhomogeneous broadening effects in lifetime measurements. In this report, recent progress in the development of ultrafast time-resolved spectroscopic techniques for interrogating single nanostructures will be discussed. The techniques include far-field experiments that utilize high numerical aperture (NA) microscope objectives, near-field scanning optical microscopy (NSOM) measurements, ultrafast electron microscopy (UEM), and time-resolved x-ray diffraction experiments. Examples will be given of the application of these techniques to studying energy relaxation processes in nanoparticles, and the motion of plasmons, excitons and/or charge carriers in different types of nanostructures.